SOSIALISASI MENUMBUHKAN JIWA BERWIRAUSAHA GUNA MENJADIKAN ENTERPRENEUR YANG SUKSES PADA MASYARAKAT DESA TOAPAYA SELATAN - Satriadi Satriadi; Anggia Sekar Putri; Armansyah Armansyah; Yuritanto Yuritanto; Diana Diana; Josephine Adriyanata; Rudy Hardianto; Sri Juliana; Suci Rahmadani (Bajang Institute, 2023)
This community service is aimed at the people of South Toapaya Village, bearing in mind that this village is the majority of the population's livelihood as entrepreneurs and gardening, this will provide an illustration so that an entrepreneurial spirit emerges from the community by starting businesses that are more productive and routine. Fostering an interest in entrepreneurship is the most important thing to do early on in order to build community courage and motivation to improve well-being by extracting abilities and skills inside to increase income, not only for individuals but also for society as an effort to overcome the problem of unemployment and reduce unemployment witch tyrannize. The research method used in the implementation of this Community Service Program is in the form of planning, implementation, evaluation. Increasing knowledge of entrepreneurship will increase public interest in establishing a business with motivation resulting from the benefits of entrepreneurship. Through a productive business which is a series of activities aimed at increasing the ability to access economic resources, increasing the ability of economic businesses, increasing work productivity, increasing savings income and creating mutually beneficial business partnerships, so that the purpose of this community service is to foster an entrepreneurial spirit by starting a business productive in the people of South Toapaya Village